Pemahaman Nadzir dalam Proses Pendaftaran Harta Benda Wakaf di Kantor Urusan Agama (KUA) Kecamatan Batipuah Kabupaten Tanah Datar - Desi Mardayanti (ZAWA: Management of Zakat and Waqf Journal, 2022)
Nadzir's Understanding in the Registration Process of Waqf Assets at the Office of Religious Affairs (KUA) of Baipuah District, Tanah Datar Regency. The purpose of this discussion is to find out how nadzir's understanding is in the process of registering waqf assets at the Religious Affairs Office (KUA) of Batipuah District, Tanah Datar Regency and how the process of registering waqf assets is at the Office of Religious Affairs (KUA) of Batipuah District, Tanah Datar Regency. The research method that the author uses is (field research) field research with qualitative descriptive methods. The data collection technique that the writer used was field observation, interviews with the Nadzir of Batipuah District and documentation. Data processing techniques are descriptive qualitative, namely collecting data related to the problem, then reading and analyzing, then analyzing the data obtained with various theoretical foundations and finally drawing conclusions. From the research that the authors conducted in the field, it can be interpreted that nadzir's understanding of the process of registering waqf assets after conducting research turns out that understanding in the process of registering waqf assets by nadzirs is divided into 3 groups, namely of the 6 people interviewed by the author there are 70% included in the understanding low related to the process of registering waqf assets, 20% including moderate understanding or understanding and 10% including high understanding because they already understand the process of registering waqf assets